FARMERS PERCEPTIONS ON RICE MECHANIZATION IN THE KOLE LANDS OF THRISSUR DISTRICT, KERALA, INDIA - P. INDIRA DEVI, N. MRIDULA and (The Journal of Research, PJTSAU, 2017)
The Kole lands of Kerala are unique agro ecosystems where rice cultivation is taken up for food security as well as ecosystem sustainability. Mechanization in the rice fields of Kole lands has been a successful step to solve the problem of labor shortage, high wages and drudgery while using the resources efficiently. The present study was conducted to understand the perception of the Kole farmers of Puzhakkal and Mullassery block panchayats of Thrissur district on the different implications of rice mechanization. While expressing the need for mechanization highlighting its advantages, the farmers also reported the constraints that demand urgent addressal, which included setting up of an effective system to ensure the availability of agro machinery in a timely manner and at affordable rents, facilities for agro machinery servicing as well as more number of skilloriented training in the farm mechanization sector.